DESIGNING THE QUALITY OF PHYSICS GRADUATES: A SYSTEMATIC EXPLORATION OF BASIC PHYSICS PRACTICUMS ALIGNED WITH 21ST CENTURY COMPETENCIES - Alfi Mufidah; Sentot Kusairi; Hartatiek; Wirawan Fadly (INSECTA: Integrative Science Education and Teaching Activity Journal, 2026)
Physics education programs must produce graduates capable of transforming scientific principles into innovative solutions. However, a significant gap exists in the systematic integration of laboratory design, standardized 21st-century competency assessments, and SDG 4-relevant outcomes. This study addresses this fragmentation by exploring basic physics laboratory models through a Systematic Literature Review (SLR) and bibliometric analysis of 22 selected articles from 2015–2025. Findings confirm a paradigm shift toward competency-based teaching, with research interest in technology integration peaking in 2023. The analysis identifies that inquiry-based models, such as the Higher Order Thinking Laboratory (HOT Lab), are most effective for fostering graduate work-readiness by prioritizing critical thinking and problem-solving. Furthermore, the study highlights the indispensable role of laboratory assistants as pedagogical agents whose 4C competencies significantly catalyze students' experimental comprehension. The study’s primary novelty is the formulation of the "Triple-Aligned Architecture," a framework ensuring that instructional objectives, digital technology integration, and evaluations systematically converge on three pillars: 21st-century skills, professional competencies, and sustainability. This architecture provides a strategic roadmap for institutions to transform laboratories into innovation hubs that produce adaptive graduates with measurable global impact and readiness for the digital era.